Industry eco-innovation strategies for process upgrading: systemic limits of internalising externalities. Issue 2 (7th February 2016) - Levidow, Les; Blind, Michiel; Lindgaard-Jørgensen, Palle; Nilsson, Åsa; Alongi Skenhall, Sara
ABSTRACT: Industry has been upgrading its production processes through eco-innovation combining environmental and economic benefits, thus reducing some resource burdens which otherwise lie outside economic accounting. Some companies have shown interest in evaluating investment options for resource burdens and total value added across a whole-system value chain. Our EC research project developed a method for whole-system assessment of eco-innovation with multi-stakeholder cooperation. In three cases presented here, tensions arise among various aims, resource burdens, system levels, beneficiaries and timescales, thus complicating the concept of eco-innovation as a win–win strategy. Radical eco-innovation would depend on extra functions, value-chain actors and resource usages which can provide greater overall benefits. But such investment faces many systemic obstacles. Eco-innovation remains path dependent, thus limiting the scope to internalise environmental externalities. The tensions and difficulties cast doubt on an EC strategy emphasising uptake of eco-innovative technologies as the means to decouple economic growth from resource burdens.